Effect of increasing β-mannanase supplementation in diets containing copra meal on growth performance, meat quality, liver health, intestinal morphology, and nutrient utilization in broiler chickens - Lee, Eun Cheol; Kim, Kang Hyeon; Kang, Min Sung; Kim, Deok Yun; Mugeniwayesu, Charline; Kil, Dong Yong (Animal bioscience, 2024)
Objective: The current study aimed to investigate the effect of increasing β-mannanase supplementation in diets containing copra meal (CM) on growth performance, meat quality, liver health, intestinal morphology, and nutrient utilization in broiler chickens.Methods: A total of 1,600 3-d-old Ross 308 broiler chickens (initial body weight±standard deviation = 43.3±1.08 g) were randomly allotted to 1 of 5 treatment groups with 8 replicates. One group was fed a corn-soybean meal-based diet (control). Other 4 diets were prepared by inclusion of 10% commercial CM in the control diet with 0, 400, 800, and 1,600 U β-mannanase/kg. Experiments lasted for 32 d.Results: Birds fed the control diet had less (p = 0.001) feed conversion ratio (FCR) than those fed diets containing 10% CM without β-mannanase supplementation. Increasing supplementation of β-mannanase in diets containing 10% CM had no linear and quadratic effects on body weight gain, feed intake, and FCR in broiler chickens. The control diet had greater (p<0.01) apparent total tract retention (ATTR) of dry matter (DM), gross energy (GE), and N as compared to the diets containing 10% CM without β-mannanase supplementation; however, no differences in the ATTR of Ca and P were identified between 2 diets. There were no linear and quadratic effects of increasing supplementation of β-mannanase on the ATTR of DM, GE, N, Ca, and P in broiler diets containing 10% CM. Both inclusion of 10% CM and increasing supplementation of β-mannanase in broiler diets did not affect apparent metabolizable energy (AME) and N-corrected AME (AMEn) values in treatment diets.Conclusion: The use of 10% CM in broiler diets during growing and finishing period impairs growth performance by decreasing energy and nutrient utilization in diets. Increasing β-mannanase supplementation in diets containing 10% CM has no positive effects on performance, meat quality, liver health, intestinal morphology, and nutrient utilization in broiler chickens.